Comparison of the effect of different methods of treadmill aerobic exercise on the expression of angiogenesis genes in adipose tissue of rats - Saed Dastaan; Saeid Naghibi; Maryam Vatandoust (Shahid Beheshti University, 2023)
Background and Purpose: The expansion of fat tissue depends on its angiogenesis rate, and exercise affect on various angiogenic factors in this tissue. With the expansion of fat tissue and adipogenesis, a dense and closed capillary network is formed in this tissue, which can suppress angiogenic factors. If there is a wide capillary network and angiogenic factors such as VEGF-A in this tissue, the expansion of fat tissue can be prevented. The aim of this study was to investigate and compare the effect of a variety of endurance training on the expression of angiogenic genes of vascular endothelial growth factor (VEGF-A) and thrombospondin-1 (TSP-1) in the subcutaneous fat tissue of rats. Materials and Methods: In this experimental study, 32 male Wistar rats aged eight weeks and weighing 237±33 grams were randomly divided into four equal groups of control, high-intensity progressive continuous aerobic training (HIT), moderate-intensity continuous aerobic training (MIT) and, high-intensity interval aerobic training (HIIT). The treadmill training protocols were conducted for eight weeks, five sessions per week, where the HIT training consisted of running at a speed of 20 m/min or at an intensity of 65% of the maximum oxygen consumption (VO2max), with a gradually increasing slope for 30 minutes. MIT training consisted of running at an intensity of 65% VO2max for 37 minutes, and HIIT training consisted of four high-intensity intervals with four minutes of running at an intensity of 90-100% VO2max and four low-intensity intervals with a duration of three minutes at 50-60% VO2max (28 minutes in total). Finally, 48 hours after the last training session, the subcutaneous fat tissue was isolated and the expression of VEGF-A and TSP-1 genes in the subcutaneous fat tissue was measured by RT-qPCR technique. The data were analyzed using a one-way analysis of variance and Tukey's post hoc test, and the significance level was considered P≤0.05. Results: Statistical analyses showed that all three exercise interventions significantly increased the expression of the VEGF-A gene in subcutaneous fat tissue. However, only HIT training could significantly reduce the expression of TSP-1 in this tissue (P˂0.05). In addition, the increase in VEGF-A expression was significantly higher after HIT training compared to HIIT (P˂0.05). Conclusion: According to the findings of this study, high-intensity progressive continuous aerobic training is probably the most desirable training to increase angiogenesis in subcutaneous fat tissue. These types of exercises can be effective in reducing fat mass by improving blood supply to fat tissue. Keywords: Exercise Training, Angiogenesis, Adipose Tissue, Thrombospondin-1